Acceptance of the disease by patients over 70 with chronic heart failure - Danuta Sternal; Ewa Dzięcielska; Ewelina Bąk (Kazimierz Wielki University, 2023)
Introduction: Chronic circulatory failure is a very serious and complex problem, constituting a significant health problem not only in Poland, but also worldwide. Treated patients with chronic circulatory failure in everyday life experience many limitations and requirements from the disease, which in many respects is difficult to accept. Aim: Diagnosing the disease acceptance rate and understanding the impact of sociodemographic variables, variables specific to clinical parameters, on the degree of disease acceptance by patients with chronic heart failure hospitalized in the hospital. Materials and methods: The research was carried out using the diagnostic survey method, using the author's own questionnaire and the AIS disease acceptance scale. The study was conducted among 98 patients of the Cardiology Department of the Railway Hospital in Wilkowice-Bystra. Results: The analysis of the degree of acceptance of the disease gives an average value of 21.49. The obtained result is in the lower limit of the reference range, indicating an average level of disease acceptance and adaptation to functioning in everyday life with its presence, while the obtained minimum value (8) and Q1 (17) indicate a low disease acceptance rate. Conclusions: On the basis of the conducted research, it is found that the average and low rate of accepting the disease by the subjects and adapting to it with a sense of psychological discomfort resulting from its presence in everyday life.